Oesophageal manometry in the evaluation of megacolon with onset in adult life. Issue 2 (February 1997) - Basilisco, G; Velio, P; Bianchi, P A
Abstract : BACKGROUND: Oesophageal motility is often impaired in patients with megaduodenum and other forms of intestinal pseudo-obstruction in which a visceral myopathy or neuropathy may be present. Idiopathic longstanding megacolon with onset in adult life is still a poorly defined entity, which may also be part of a more widespread motility disorder but in which oesophageal motility has not been yet systematically studied. AIMS: To assess oesophageal motility in patients with longstanding idiopathic megacolon with onset in adult life. PATIENTS: 14 consecutive subjects with idiopathic megacolon whose symptoms began after the age of 10 and a clinical history of 2-22 years. METHODS: Standard barium enema, water perfused oesophageal manometry, and also anorectal manometry. RESULTS: Oesophageal motility was impaired in five patients (36%; 95% confidence intervals 16 to 61%). Normal peristalsis was substituted by low amplitude multiple peaked simultaneous contractions in four subjects and by undetectable contractions in one. In three of them the lower oesophageal sphincter did not relax after swallows; in the same patients anal relaxation after rectal distension was also undetectable. All five patients with impaired oesophageal motility had a colonic dilatation sparing the rectum. Three of them reported constipation and a history of pesudo-obstruction and the other two only abdominal distension. CONCLUSIONS: Oesophageal manometry should be performed in patients with longstanding idiopathic megacolon with onset in adult life, in particular if the rectum is not dilated and even in absence of pseudo-obstruction. This simple test may disclose a more widespread visceral neuropathy or myopathy. Such a diagnosis helps to better understand the cause of the colonic dilatation and may be clinically relevant for treatment of the patients.